Global advertising in a global culture - Gould, Thomas H. P., 1953-2016 (Rowman and Littlefield, 2016)
Gould explores the commercial and cultural underpinnings of advertising-and how this form of communication is evolving into a platform for change at the individual, social, and even political levels.